Building bridges: a Qualitative exploration of the athlete - guide partnership in high-performance parasport - Mannella, S.; Bundon, A. (Qualitative Research in Sport, Exercise and Health, 2023)
Individuals who are visually impaired compete in Paralympic sports with the help of their sighted guides. The guide participates alongside the athlete, and the pair seek to achieve optimal performance together. The partnership transforms many sports -typically understood to be individual- into team sports, yet little is known about this unique sport relationship. The purpose of this study was to explore how the athlete - guide partnership challenges and reproduces normative assumptions of bodies, abilities, and high-performance sport. The study was informed by a critical interpretivist paradigm and included interviews with both athletes and guides from six high-performance athlete - guide pairs (12 interviews). The data were analysed through a reflexive thematic analysis and two themes were constructed. Changing `Visibility`: Reshaping Perspectives Through the Athlete - Guide Partnership illustrates how being part of the athlete - guide partnership led participants to different understandings about high-performance sport and disability. Tandeming Sport Systems Built for One demonstrates the challenges participants encountered navigating in tandem sport systems intended to support solo athletes. The findings suggest that the athlete - guide partnership creates inclusivity in Para sport by allowing athletes to fully participate. However, the partnership is also exposed to detrimental aspects of high-performance sport environments that prioritise performance rather than athlete well-being. The findings contribute to a growing body of critical disability sport scholarship that calls out ableism in sport. It also can inform the practices of the sport sector with the aim of better understanding and supporting the needs of visually impaired athletes.